2021
DOI: 10.1021/acs.est.0c06310
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Oxyanions on Redox-driven Transformation of Layered Manganese Oxides

Abstract: Layered manganese (Mn) oxides, such as birnessite, can reductively transform into other phases and thereby affect the environmental behavior of Mn oxides. Solution chemistry strongly influences the transformation, but the effects of oxyanions remain unknown. We determined the products and rates of Mn­(II)-driven reductive transformation of δ-MnO2, a nanoparticulate hexagonal birnessite, in the presence of phosphate or silicate at pH 6–8 and a wide range of Mn­(II)/MnO2 molar ratios. Without the oxyanions, δ-Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 79 publications
(192 reference statements)
0
9
0
Order By: Relevance
“…can be generated at high Mn(II)/MnO2 ratios (0.5 and 1). 60 In our XRD patterns, broad bands (hump) have appeared between 12° and 22° and between 25° and 35° in the samples reacted with Mn(II) (Mn(II)/MnO2 molar ratio = 0.3) or H2O2 (H2O2/MnO2 molar ratio = 0.6), suggesting changes in the structure or ordering of the birnessite mineral sheets (Fig. 4).…”
Section: Effects Of Mn(ⅱ) On the Removal Capacity Of Mnomentioning
confidence: 80%
See 1 more Smart Citation
“…can be generated at high Mn(II)/MnO2 ratios (0.5 and 1). 60 In our XRD patterns, broad bands (hump) have appeared between 12° and 22° and between 25° and 35° in the samples reacted with Mn(II) (Mn(II)/MnO2 molar ratio = 0.3) or H2O2 (H2O2/MnO2 molar ratio = 0.6), suggesting changes in the structure or ordering of the birnessite mineral sheets (Fig. 4).…”
Section: Effects Of Mn(ⅱ) On the Removal Capacity Of Mnomentioning
confidence: 80%
“…It was previously reported that unlike nitrate, silicate or phosphate may interact with MnO2 through hydrogen bonding or formation of outer-sphere complexes with surface hydroxyl groups of MnO2. [59][60][61][62] On the other hand, previous studies reported that the presence of dissolved silicate may decrease the oxidation rate constants of MnO2 toward chlorinated compounds. 63,64 They have attributed the decrease in MnO2 reactivity to the surface-bound silicate but none of them have provided adsorption data of silicate onto MnO2.…”
Section: Synergistic Effects Of Anions and H 2 O 2 On The Oxidative Activity Of Mnomentioning
confidence: 98%
“…Dissolved silicate tends to adsorb onto colloidal MnO 2 by hydrogen bonds and cover the MnO 2 surface; further particle aggregation and growth are inhibited accordingly . Additionally, phosphate and silicate form oxygen anion ternary complex with Mn­(II,III) at the vacancy of MnO 2 and interfere with the electron transfer and structure arrangement . This effect inhibits the adsorption of iodine accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…43 Additionally, phosphate and silicate form oxygen anion ternary complex with Mn(II,III) at the vacancy of MnO 2 and interfere with the electron transfer and structure arrangement. 44 This effect inhibits the adsorption of iodine accordingly. These anions compete for and occupy the active sites on the γ-MnO 2 surfaces, and iodine removal is inhibited by these different mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…9 Additionally, by studying Raman spectra and transformation behavior of MnO 2 nanoparticles in the presence of various oxyanions, a generalized effect of oxyanions on the structural alteration in MnO 2 has been proposed, including adjustment in the size, average Mn valence, oxygen species, and preferentially exposed planes of MnO 2 . 13,18,19 These structural characteristics are crucial for determining the oxidative and catalytic capacity of MnO 2 . 15,20 Therefore, oxyanions may affect the degradation efficiency of Mn(VII) by controlling the oxidative and catalytic capacity of MnO 2 .…”
Section: ■ Introductionmentioning
confidence: 99%